Measurement of a compact Boomarang-shaped microstrip antenna for wireless sensor network applications. (August 2021) - Shakib, M.N.; Moghavvemi, M.; Rahman, M.A.; Ramli, R.M.; Lim, H.S.; Ahmed, M.R.
Abstract: The miniaturization of electronic devices has facilitated increasing interest in new applications of wireless communication. In this paper, a new miniature microstrip fed boomerang-shaped patch antenna has been proposed and designed for a wireless sensor network (WSN) application. In this design, the proposed antenna possesses a wide bandwidth by loading of a boomerang-shaped patch; with a 50 Ω microstrip feed line and a partial ground plane. A one-step staircase slot is embedded in the ground plane to enhance the impedance matching over a wide frequency range. The antenna occupies a small size of 10 × 12 mm 2, or 1.2 cm 2 . The simulated results are verified with measured results. The measured result shows that the achievable bandwidth of 69% (8.48–17.45 GHz). The antenna possesses stable radiation patterns and acceptable gain. The proposed low profile antenna is suitable to integrate with sensors for wireless sensor network in X-band and Ku band applications.